1993
DOI: 10.1002/j.1460-2075.1993.tb05878.x
|View full text |Cite
|
Sign up to set email alerts
|

Protocadherins: a large family of cadherin-related molecules in central nervous system.

Abstract: Using the polymerase chain reaction, we have isolated numerous rat and human cDNAs of which the deduced amino acid sequences are highly homologous to the sequences of the extracellular domain of cadherins. The entire putative coding sequences for two human proteins defined by two of these cDNAs have been determined. The overall structure of these molecules is very similar to that of classic cadherins, but they have some unique features. The extracellular domains are composed of six or seven subdomains that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
287
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(295 citation statements)
references
References 46 publications
6
287
0
2
Order By: Relevance
“…Interaction of the γ-Pcdh C-terminal constant domain with FAK and PYK2 was demonstrated to inhibit the activity of these tyrosine kinases (14), and the γ-Pcdhs also can inhibit canonical Wnt signaling in vitro (15). Cell adhesion mediated by trans interactions between clustered Pcdhs has been reported in several studies (7,(16)(17)(18)(19)(20)(21). With one exception (19), the sparse extant data are consistent with a cadherin-like homophilic mode of Pcdh interaction.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Interaction of the γ-Pcdh C-terminal constant domain with FAK and PYK2 was demonstrated to inhibit the activity of these tyrosine kinases (14), and the γ-Pcdhs also can inhibit canonical Wnt signaling in vitro (15). Cell adhesion mediated by trans interactions between clustered Pcdhs has been reported in several studies (7,(16)(17)(18)(19)(20)(21). With one exception (19), the sparse extant data are consistent with a cadherin-like homophilic mode of Pcdh interaction.…”
mentioning
confidence: 67%
“…Previous studies of interactions among clustered Pcdhs used a wide variety of methods, including aggregation of transfected L929 cells (16,17), K562 cells (20), or HEK293 cells (7); recruitment of Pcdhs to cell-cell contacts in HEK293 cells (18,21); and aggregation of beads coated with ectodomains (19). We tested several of these methods and found that only cell aggregation assays using the human leukemia line K562 were suitable for our experiments.…”
Section: γ-Pcdhs Mediate Trans Interactions With Properties Distinct mentioning
confidence: 99%
“…DISCUSSION In this report, we have described the isolation of a novel type II human cadherin molecule. Although many cadherins and cadherin-related molecules have been isolated by PCR (10,25), this is the first report of a cadherin molecule being isolated by virtue of its association with ␤-catenin. Cadherin-14 has several cytoplasmic amino acid sequences that differ from those used for PCR cloning.…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 95%
“…Primers for protocadherin, pc-f2 (forward) and r2 (reverse), were virtually identical to those described previously (Sano et al, 1993). The sequences were 5Ј-CCG AAT TCA ARS SNN TNG AYT WYG A-3Ј and 5Ј-CCG GAT CCN NNG GNG CRT TRT CRT T-3Ј, respectively.…”
Section: Oligonucleotides For Cadherins and Protocadherinsmentioning
confidence: 99%